Complex Artificial Environments Simulation, Cognition and VR in the Study and Planning of Cities - Portugali, Juval (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This book explores the possibilities of applying the theories of complexity and self-organization developed to account for various phenomena in the natural science to artifacts traditionally the realm of humanities and social sciences. The emphasis of this volume is on the development of cities and the impact of these methods on urban simulation methods.